Corporate Governance memoderasi Related Party Transaction dan Financial Distress terhadap Penghindaran Pajak - Widodo, Yulfian Ibnu Cahyo; Nofryanti, Nofryanti; Rosini, Iin (Universitas Batanghari Jambi, 2024)
This study aims to examine the influence of related party transactions and financial difficulties on tax avoidance with corporate governance as moderating variable. corporate governance. This research uses a population of 92 companies in the consumer goods industry sector listed on the IDX in 2018-2022. The research sample was carried out using a purposive sampling method and obtained 125 company data that met the criteria. The data used is secondary data in the form of financial reports and company annual reports. Data were analyzed using a panel data regression analysis model and moderate regression analysis (MRA) test with E-Views 12 software. According to the findings of the study, related party transactions and financial distress have an effect on tax avoidance. Corporate governance cannot moderate the influence of related party transactions on tax avoidance. Corporate governance cannot moderate the influence of financial distress on tax avoidance.